2017
DOI: 10.1007/s00281-017-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary activation of the complement system and its importance for the pathophysiology of clinical conditions

Abstract: Activation and regulation of the cascade systems of the blood (the complement system, the coagulation/contact activation/kallikrein system, and the fibrinolytic system) occurs via activation of zymogen molecules to specific active proteolytic enzymes. Despite the fact that the generated proteases are all present together in the blood, under physiological conditions, the activity of the generated proteases is controlled by endogenous protease inhibitors. Consequently, there is remarkable little crosstalk betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 148 publications
0
25
0
Order By: Relevance
“…Given that ECLS in itself is known to increase complement activation products ( 22 , 23 ), we analyzed their levels in subjects (from both cohorts) who received ECLS compared with those who did not. In the Penn cohort, the median sC4d levels were comparable (median, interquartile range [IQR, ng/mL]: 365, 201.2–624.8 in those who received ECLS, compared with 241.2: 111–590.1 in those who did not, P = 0.3) as were the median sC5b-9 levels (median, IQR, ng/mL: 499, 114–1027 in those who received ECLS, compared with 294, 60–960 in those who did not, P = 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…Given that ECLS in itself is known to increase complement activation products ( 22 , 23 ), we analyzed their levels in subjects (from both cohorts) who received ECLS compared with those who did not. In the Penn cohort, the median sC4d levels were comparable (median, interquartile range [IQR, ng/mL]: 365, 201.2–624.8 in those who received ECLS, compared with 241.2: 111–590.1 in those who did not, P = 0.3) as were the median sC5b-9 levels (median, IQR, ng/mL: 499, 114–1027 in those who received ECLS, compared with 294, 60–960 in those who did not, P = 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation has been long proposed that is responsible for the stable maintenance of gene expression patterns [41,46]. Specifically, DNA methylation establishes a silent chromatin state by collaborating with proteins that modify nucleosomes [43]. Importantly, our results showed that DNA methylation was altered in serpinina1 gene encoding for alpha-1 antiproteinase antitrypsin.…”
Section: Discussionmentioning
confidence: 65%
“…Alpha-1 antiproteinase antitrypsin is widely distributed in body fluids, and its concentration is especially increased in acute inflammatory responses. Importantly, in intestinal epithelia, it is suggested that alpha-1 antiproteinase antitrypsin may be an important self-protective mechanism against various proteases such as the pancreatic proteolytic enzymes as well as and collagenase released from leucocytes [43]. As salivary and pancreatic glands secrete similar proteases and have similar structure involving acini and the ductal system, it could be suggested that alpha 1 antiproteinase antitrypsin could be part of the self-defence mechanism in salivary glands as well.…”
Section: Discussionmentioning
confidence: 99%
“…The primary ignition mechanism—whether complement or coagulation activation—at the site of antibody binding is not clear; however, once activated, complement and coagulation then engage in a complex set of interactions(54). TMA may be considered to be a consequence of this thromboinflammatory fire, and its severity potentially related to the combination of donor and recipient characteristics to both propel or inhibit the ensuing effects.…”
Section: Introductionmentioning
confidence: 99%